Efficacy and Safety of External Versus Internal Stenting in Children with Open Pyeloplasty for Primary Ureteropelvic Junction Obstruction. A Single Centre Experience - Syed Ghafar Shah, Irfan Ullah, Muhammad Kamran Khan, Yasir Ali, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Ureteropelvic junction obstruction (UPJO), a condition, stops urine from freely passing from the renal pelvis to the ureter. It is a common urological condition, with a male to female ratio of 2:1 and an incidence of 1 in 500 (1). UPJ obstruction may be caused by inherited and acquired diseases. The majority of cases are congenital due to intrinsic or extrinsic causes (2). Objective: To determine the efficacy and safety of external versus internal stenting in children with primary Ureteropelvic junction obstruction. Material and Methods: At the Institute of Kidney Diseases in Hayatabad, Peshawar, Pakistan, a randomized controlled study was carried out from January 2021 to December 2021. Patients were split into two groups based on the kind of stent that was used. All patients with DJ stents were placed in Group A, and patients with PU stents (5–6 Fr feeding tubes) that passed through the kidney parenchyma on their way from the ureteropelvic junction to the skin belonged in Group B. Results: 80 people in total (55 men and 25 women) were enrolled in the study. In groups A and B, the mean ages at surgery were 3.4 and 3.9 years respectively. Table 1 displays the patient's demographics and surgical factors. The two groups' mean operating times (124 ±3.4 for group A and 130 ± 3.1 for group B) were comparable. The DJS group's stent duration ranged from 3 to 4 weeks, with a mean of 27 days, while the PU group's ranged from 1 to 2 weeks, with a mean of 13 days. In DJS and PU stent, the median hospital stay was 1.3 and 2.8 days, respectively. Practical Implication: The surgeon must compare the inconvenience of a second anaesthesia, the cost, and the DJ stent's potential for complications against the longer hospital stay that comes with PU stenting and advise parents accordingly. Conclusion: According to our findings, the complication rates and mean operating time for both types of stents were comparable. Even though the DJS stent requires less recovery time than the PU stent, its removal still required a second anaesthesia Keywords: External Versus, surgical factors, ureteropelvic junction obstruction, urine, Congenital